96.5k views
1 vote
Simplify the following.
7² =
4⁰ =
6-¹=

User Praytic
by
5.1k points

2 Answers

6 votes

Answer:

  • 49
  • 1

Explanation:

hey

please like my question

User Peter Jerald
by
6.0k points
2 votes

Answer:

49

1

1/6

Explanation:

7^2 is just 7 * 7 = 49

4^0 = 1, since anything to the power of 0, is 1.


6^(-1) is equal to
(1)/(6) since
((a)/(b))^(-x)=((b)/(a))^x=(b^x)/(a^x). Whenever you have a negative exponent, you flip the fraction, in this case the fraction is 6/1 so it becomes 1/6. then distribute the exponent across the division and you get 1^1/6^1 which is just 1/6